2017
DOI: 10.1590/1981-22562017020.160101
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an instrument for the prognostic evaluation of elderly persons in intensive care units

Abstract: Objective: To create an instrument for the prognostic evaluation of elderly patients hospitalized in an intensive care unit. Methods: A cohort study, with prospective data collection, which included elderly persons aged 60 years or older, was carried out in the city of João Pessoa, in the state of Paraíba, Brazil. Data collection was performed using an instrument created from a pilot study and the Katz Index. Poisson's regression was used for data analysis. This technique estimates relative risk, retaining var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Thus, age alone is not related to the worst prognosis, but other associated factors, such as severity of acute illness, comorbidities and functional status, may contribute to the worst prognosis. 25 It was observed predominance of men in ICU admissions. 10,15-18-21,23-24,26 A longitudinal study on the clinical and laboratory characteristics and clinical outcome of septic and non-septic patients admitted to the ICU showed that the male sex was more associated with admission due to sepsis in this service.…”
Section: Aspiration Of Secretionsmentioning
confidence: 98%
See 2 more Smart Citations
“…Thus, age alone is not related to the worst prognosis, but other associated factors, such as severity of acute illness, comorbidities and functional status, may contribute to the worst prognosis. 25 It was observed predominance of men in ICU admissions. 10,15-18-21,23-24,26 A longitudinal study on the clinical and laboratory characteristics and clinical outcome of septic and non-septic patients admitted to the ICU showed that the male sex was more associated with admission due to sepsis in this service.…”
Section: Aspiration Of Secretionsmentioning
confidence: 98%
“…26 So, men have a higher frequency of hospitalization in these units because they use primary and secondary health care services less frequently. 25 In this context, it is extremely important to implement the lines of action of the National Policy for Comprehensive Care to Men's Health for recognizing that male diseases constitute real public health problems and thus enabling strategies and actions planned for this public so as to reduce morbidity and mortality rates due to preventable causes in this population. This will make it possible to improve quality of life expectancy.…”
Section: Aspiration Of Secretionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Os gerontes, em internamento hospitalar, não raramente demandam leitos em UTI, evoluindo mais facilmente a um estado crítico, o que determina maior tempo de tratamento e, por conseguinte, custos (Pedrosa et al, 2017). Diante de quadros críticos, é de extrema importância proceder com uma terapia nutricional (TN) eficaz para o paciente idoso, diagnosticando déficits nutricionais e intervindo o mais precocemente possível, a fim de evitar maior degradação nutricional, com a qual se associa piores desfechos, visto que é um grupo mais suscetível.…”
Section: Introductionunclassified
“…There has been an increase in the number of elderly patients who receive therapy in the hospital and intensive care unit due to increase in the elderly population in the community. There has also been an increase in the rate of admission to the hospital, and thereby, to the intensive care unit (1). The course of elderly patients in intensive care differs in various aspects from that of young patients.…”
Section: Introductionmentioning
confidence: 99%